Elder abuse and neglect: an overlooked patient safety issue. A focus group study of nursing home leaders' perceptions of elder abuse and neglect - Janne Myhre; Susan Saga; Wenche Malmedal; Joan Ostaszkiewicz; Sigrid Nakrem (BMC, 2020)
Abstract Background The definition and understanding of elder abuse and neglect in nursing homes can vary in different jurisdictions as well as among health care staff, researchers, family members and residents themselves. Different understandings of what constitutes abuse and its severity make it difficult to compare findings in the literature on elder abuse in nursing homes and complicate identification, reporting, and managing the problem. Knowledge about nursing home leaders' perceptions of elder abuse and neglect is of particular interest since their understanding of the phenomenon will affect what they signal to staff as important to report and how they investigate adverse events to ensure residents' safety. The aim of the study was to explore nursing home leaders' perceptions of elder abuse and neglect. Methods A qualitative exploratory study with six focus group interviews with 28 nursing home leaders in the role of care managers was conducted. Nursing home leaders' perceptions of different types of abuse within different situations were explored. The constant comparative method was used to analyse the data. Results The results of this study indicate that elder abuse and neglect are an overlooked patient safety issue. Three analytical categories emerged from the analyses: 1) Abuse from co-residents: 'A normal part of nursing home life'; resident-to-resident aggression appeared to be so commonplace that care leaders perceived it as normal and had no strategy for handling it; 2) Abuse from relatives: 'A private affair'; relatives with abusive behaviour visiting nursing homes residents was described as difficult and something that should be kept between the resident and the relatives; 3) Abuse from direct-care staff: 'An unthinkable event'; staff-to-resident abuse was considered to be difficult to talk about and viewed as not being in accordance with the leaders' trust in their employees. Conclusions Findings in the present study show that care managers lack awareness of elder abuse and neglect, and that elder abuse is an overlooked patient safety issue. The consequence is that nursing home residents are at risk of being harmed and distressed. Care managers lack knowledge and strategies to identify and adequately manage abuse and neglect in nursing homes.